A robótica educacional e a plataforma Arduino : estratégias construcionistas para a prática docente - Luciano, Ana Paula Giacomassi (2017)
Current society lacks professionals who present skills and relevant knowledge to the current new paradigms. Therefore, it becomes essential to rethink the attitudes regarding training of professionals, which directly affects the structures of professional identity of each individual. The physical sciences have made great progress and the achievements of such sciences foster the technology and engineering that produces various technological devices for society. However, ignorance of the links between science, technology and society often deters the teaching profession often from using such technologies to bring the student's experience closer to a society technologically advanced with basic scientific theory. The present work emerged from the questioning if the educational robotics approach with the Arduino platform, following the constructivist assumptions, can modify the attitudes of graduates and later influence the teaching practices with a view to the construction of the professional identity. Thus, the central objective of this thesis is to evaluate the contribution of educational robotics, with the use of Arduino platform and it is supported methodologically by constructionism, in the modification of the teaching activity of students of the initial formation of the Physics course as well as their professional identity. Thus, we offer workshops related to the Arduino open source platform and educational robotics to 25 students of the Physics undergraduate program belonging to the Institutional Program of Initiation to Teaching Grant (PIBID). The theoretical assumption adopted to support our action in this work is Papert's Theory of Constructionism. We collected data referring to the graduates a priori through a semistructured interview. We made video and audio recordings during workshops. With the purpose of examining the teaching actions of the graduates, they taught a workshop for 8 academics from the State University of Maringá, as part of the academic week of the course. Thus, through the observation of this workshop as well as the realization of a focal analysis group, we evaluate these actions with respect to the use of constructionism in the use of new technologies in teaching. We organized the analysis in three main themes with the respective categories of each one and our referential adopted to analyze the data collected was based on the Discursive Textual Analysis. Therefore, we have been able to identify that in order to really change the future teaching practices and achieve the construction of the teaching identity, it is necessary for the student to know and experience during his / her initial formation a methodology that provides necessary subsidies for the development of skills and knowledge related to Teaching.